Pengendalian Berat Badan Lahir Rendah (BBLR) dengan Pendekatan Asset Based Community Development (ABCD) di Puskesmas Kota Makassar - Rosdianah Rahim; Nadyah Haruna; Muhammad Nur Alamsyah Rajab; Yusril Ihsanul (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Low Birth Weight (LBW) is a birth weight of less than 2500 grams which is an indicator of a child's growth and development until adulthood and describes the nutritional status obtained by the fetus while in the womb. The community's Asset Based Community Development (ABCD) approach is used to help achieve a common goal in controlling LBW, starting with asset identification, problem analysis, potential planning, implementation, and utilization. The focus of the research was the identification of human resource assets for controlling LBW. This is qualitative research using the ABCD approach with observation and in-depth interviews. The method for choosing informants is snowball sampling in the working area of ​​the Community Health Center in Makassar City in 2022. Based on the ABCD, this study identifies several assets involved in controlling LBW cases at the Community Health Center in Makassar City: Human Assets, namely Health services related to pregnant women's programs such as ANC visits, pregnant women's classes, and knowledge of pregnant women; Social assets, Physical assets, and Economic assets depend on the profession of each resident. These four assets are very supportive to control LBW cases in the Community Health Center in Makassar City.